The Influence of Leadership Style and Work Facilities on Job Satisfaction of Civil Servants at the Regent's Office of Central Tapanuli Regency - Annisa Hazrida Effendy (International Journal of Applied Finance and Business Studies, 2020)
The research objective is to determine and analyze the Influence of Leadership Style on Job Satisfaction Work Facilities Civil Servants Central Tapanuli Regency Office. The population in this study is the entire Civil Servants in Central Tapanuli Regency Office totaling 126 employees of Civil Affairs. The method used in this research is quantitative method. The data analysis technique in this research is descriptive statistical analysis and multiple linear regression analysis. The data used are primary data and secondary data. The results of this study show that, either simultaneously or partially, leadership style and employee facilities and significant positive effect on job satisfaction of civil servants Regent Office Central Tapanuli.